2020
DOI: 10.1155/2020/8882698
|View full text |Cite
|
Sign up to set email alerts
|

Side Friction of Rock‐Socketed Piles Involving Thick Sediment

Abstract: This paper investigates the skin friction transfer characteristics of the rock-socketed section of a rock-socketed pile resting on thick sediment by conducting in situ core-drilling tests and static loading tests. Test results show that when using the impact hole-forming method in weakly cemented soil, a layer of sediment is deposited at the pile bottom. Due to the existence of sediment, when the load reaches a certain value, sudden and large subsidence is observed. This indicates that the end resistance does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Wang et al carried out the study of the friction resistance transfer characteristics of rock-socketed piles on thick sediment, and derived the complete constitutive model function of the pile-rock interface. They concluded that the smaller the rock-socketed thickness, the greater the settlement and lateral friction resistance, the relatively small rock-socketed thickness and rock strength, with the lower peak was higher than the upper peak [25]. Liu et al carried out a study on the lateral response of vertical loads to piles, and conducted a comparative analysis of the lateral response of vertical loads to rock-socketed piles in normal consolidated clay and over-consolidated clay, concluding that, with the application of vertical load, the initial lateral stiffness and ultimate bearing capacity of the normal consolidated clay increased by 10.0% and 49.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al carried out the study of the friction resistance transfer characteristics of rock-socketed piles on thick sediment, and derived the complete constitutive model function of the pile-rock interface. They concluded that the smaller the rock-socketed thickness, the greater the settlement and lateral friction resistance, the relatively small rock-socketed thickness and rock strength, with the lower peak was higher than the upper peak [25]. Liu et al carried out a study on the lateral response of vertical loads to piles, and conducted a comparative analysis of the lateral response of vertical loads to rock-socketed piles in normal consolidated clay and over-consolidated clay, concluding that, with the application of vertical load, the initial lateral stiffness and ultimate bearing capacity of the normal consolidated clay increased by 10.0% and 49.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%